2022
DOI: 10.1177/0145482x221144324
|View full text |Cite
|
Sign up to set email alerts
|

Access to Health and Disability Services for New Zealanders With Impaired Vision During the COVID-19 Pandemic 2020–2022

Abstract: Introduction: The COVID-19 pandemic has affected access to health and social services globally, leading to delays in accessing appropriate care. However, while there is a growing base of research into service access for the general population, there remains scarce information on the implications of the pandemic on disabled people. This article describes issues with health and disability support access for people with impaired vision in Aotearoa New Zealand (Aotearoa). Methods: Applying an Interpretive Descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
(13 reference statements)
1
4
0
Order By: Relevance
“…Our findings affirm that disabled New Zealanders' access to healthcare and disability support services were negatively impacted by the pandemic, consistent with extant literature [8,11,13,[21][22][23]. Our study has revealed that, while policy decisions generally negatively impacted the healthcare and disability support of disabled individuals, some policies resulted in positive outcomes for disabled people.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings affirm that disabled New Zealanders' access to healthcare and disability support services were negatively impacted by the pandemic, consistent with extant literature [8,11,13,[21][22][23]. Our study has revealed that, while policy decisions generally negatively impacted the healthcare and disability support of disabled individuals, some policies resulted in positive outcomes for disabled people.…”
Section: Discussionsupporting
confidence: 90%
“…However, the ongoing restrictions also significantly disrupted healthcare and support services, resulting in challenges for disabled people. For example, staff shortages were exacerbated by infection control measures, staff illness, and mandatory self-isolation periods, resulting in in-home support services being scaled back, disrupted, or even suspended, and many community services, such as day programmes and respite care were also negatively impacted [11][12][13].…”
Section: The New Zealand Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…Tis included restrictions on the number of visitors in hospitals, minimizing everyday movement and contact, and halting the operation of nonessential services [13]. A handful of studies have discussed older people's experiences dealing with a lag time in accessing healthcare [20] and problems with waiting in long queues [21]. Common disadvantages older people experience include having coexisting health problems, having low social support, and low or lack of sufcient income [22].…”
Section: Introductionmentioning
confidence: 99%
“…People with visual impairment are generally considered to have little social participation and social roles 9) . However, after the COVID-19 pandemic, things worsened as communities between people with visual impairment themselves were lost, 10) reducing their engagement with others in the long-term. In other words, in a prolonged pandemic, while people with sight were beginning to rejoin their communities and societies by adopting accommodative strategies against the pandemic, those with visual impairments continued to find it difficult to interact with others even under such accommodative strategies.…”
Section: Introductionmentioning
confidence: 99%